Dosimetric feasibility of real‐time MRI‐guided proton therapy. Issue 11 (24th October 2014) - Moteabbed, M.; Schuemann, J.; Paganetti, H.
Abstract : Purpose: Magnetic resonance imaging (MRI) is a prime candidate for image‐guided radiotherapy. This study was designed to assess the feasibility of real‐time MRI‐guided proton therapy by quantifying the dosimetric effects induced by the magnetic field in patients' plans and identifying the associated clinical consequences. Methods: Monte Carlo dose calculation was performed for nine patients of various treatment sites (lung, liver, prostate, brain, skull‐base, and spine) and tissue homogeneities, in the presence of 0.5 and 1.5 T magnetic fields. Dose volume histogram (DVH) parameters such as D 95, D 5, and V 20 as well as equivalent uniform dose were compared for the target and organs at risk, before and after applying the magnetic field. The authors further assessed whether the plans affected by clinically relevant dose distortions could be corrected independent of the planning system. Results: By comparing the resulting dose distributions and analyzing the respective DVHs, it was determined that despite the observed lateral beam deflection, for magnetic fields of up to 0.5 T, neither was the target coverage jeopardized nor was the dose to the nearby organs increased in all cases except for prostate. However, for a 1.5 T magnetic field, the dose distortions were more pronounced and of clinical concern in all cases except for spine. In such circumstances, the target was severely underdosed, as indicated by a decrease in D 95 of up to 41% of the prescribed dose compared to the nominal situation (no magnetic field). Sites such as liver and spine were less affected due to higher tissue homogeneity, typically smaller beam range, and the choice of beam directions. Simulations revealed that small modifications to certain plan parameters such as beam isocenter (up to 19 mm) and gantry angle (up to 10°) are sufficient to compensate for the magnetic field‐induced dose disturbances. The authors' observations indicate that the degree of required corrections strongly depends on the beam range and direction relative to the magnetic field. This method was also applicable to more heterogeneous scenarios such as skull‐base tumors. Conclusions: This study confirmed the dosimetric feasibility of real‐time MRI‐guided proton therapy and delivering a clinically acceptable dose to patients with various tumor locations within magnetic fields of up to 1.5 T. This work could serve as a guide and encouragement for further efforts toward clinical implementation of hybrid MRI–proton gantry systems.